2003
DOI: 10.1111/j.1945-5100.2003.tb01045.x
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of crystalline forsterite grain formation due to coalescence growth of Mg and SiO smoke particles

Abstract: Abstract-Experimental studies of coalescence between Mg grains and SiO grains in smoke reveal the direct production of crystalline forsterite grains. The present results also show that different materials can be produced by grain-grain collisions, which have been considered one of the models of grain formation in the interstellar medium. The fundamentals of coalescence growth in smoke, which have been developed in our series of experiments, are presented in this paper. Mg 2 Si polyhedral grains were obtained i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…In a previous paper, we demonstrated crystalline Mg 2 SiO 4 grain formation due to the coalescence and growth of Mg and SiO smoke grains (Mg-SiO system) in the case of an SiO-grain-rich atmosphere in a Mg-SiO system (Kaito et al 2003). These Mg 2 SiO 4 grains contained silicon crystallites.…”
Section: Introductionmentioning
confidence: 82%
“…In a previous paper, we demonstrated crystalline Mg 2 SiO 4 grain formation due to the coalescence and growth of Mg and SiO smoke grains (Mg-SiO system) in the case of an SiO-grain-rich atmosphere in a Mg-SiO system (Kaito et al 2003). These Mg 2 SiO 4 grains contained silicon crystallites.…”
Section: Introductionmentioning
confidence: 82%
“…In previous works, we have demonstrated that Mg 2 SiO 4 (forsterite) crystalline grains containing Si crystals could be produced by the coalescence of Mg and SiO smoke grains (Kaito et al 2003). We have also suggested that single crystalline Mg 2 SiO 4 , polycrystalline Mg 2 SiO 4 , and amorphous Mg-bearing silicate grains are produced by the coalescence of MgO and SiO 2 smoke grains (MgO-SiO 2 system) (Kamitsuji et al 2005).…”
Section: Introductionmentioning
confidence: 91%
“…In the case of our heating experiment (Kamitsuji et al 2005a;Kaito et al 2007), some crystallites produced on the surface layer acted as nuclei for further crystallization, similar to grain growth. Since the mean free path of the phonon was on the order of the crystallite size, the concentric crystallization rings appeared as dark contrasts, as indicated by arrows A and B in Figure 4.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, we succeeded in forming both amorphous Mg-bearing silicate and crystalline forsterite (Mg 2 SiO 4 ) grains by the coalescence growth of MgO and SiO 2 and/or Mg and SiO grains in a mixed smoke (Kamitsuji et al 2005b;Kaito et al 2003). During the thermal annealing process, the crystallization of Mg-bearing silicate grains into forsterite (Mg 2 SiO 4 ) was directly observed at 800ЊC starting with amorphous Mg-bearing silicate grains in a transmission electron microscope (TEM) (Kamitsuji et al 2005a).…”
Section: Introductionmentioning
confidence: 99%